Disinfection of Infected Root Canals: Nanosilver Has Good Potential. Issue 11 (5th July 2019) - Yin, Wei; Zheng, Zhong; Liu, Yaoli; Wang, Lina; Shi, Chun; Zhang, Lianlian; Liu, Shuo; Niu, Weidong; Ting, Kang; Bian, Zhuan
Abstract: Bacterial elimination is the key to the treatment of periapical periodontitis. However, existing root canal disinfectants have not fully met this requirement. Here, a new disinfectant candidate, nanosilver, is provided and its efficacy against root canal infection is analyzed. Compared to calcium hydroxide, the nanosilver, which is evenly loaded into the poly(lactic‐ co ‐glycolic acid) carrier, shows excellent bactericidal activity against free‐living Enterococcus faecalis, stable‐phase E. faecalis biofilm, and starved‐phase E. faecalis biofilm, which is difficult to eliminate through root canal therapy at present. Nanosilver also exhibits great biocompatibility as it does not affect the proliferation of primary pulp cells. In lipopolysaccharide‐triggered periapical periodontitis, the application of nanosilver significantly inhibits the expression of several inflammation‐related factors, including TLR4, Caspase‐1, and Caspase‐11. Furthermore, nanosilver also has a great anti‐inflammatory effect on inhibiting the progression of canine chronic periapical periodontitis. The quantity of E. faecalis in canals and the shadow area around the apex significantly decrease after application of 1% and 2% nanosilver for 4 weeks. It is demonstrated that 1% and 2% nanosilver has a superior ability to resist periapical periodontitis in vivo and in vitro. Abstract : Nanosilver, which is evenly loaded into the poly(lactic‐ co ‐glycolic acid) carrier, shows a great bactericidal effect against free‐living Enterococcus faecalis, stable‐phase E. faecalis biofilm, and starved‐phase E. faecalis biofilm compared to calcium hydroxide (pH 12). It also exhibits excellent biocompatibility. In canine chronic periapical periodontitis, nanosilver significantly decreases the quantity of bacterial and promotes the healing of the lesion.